(untitled) (Jurnal Bina Praja, 2020)
Researchers’ interest in studying the quality of democracy in Indonesia has been developed since the reform era. Although there was a pessimistic view on Indonesian democracy’s achievement, the quality of Indonesian democracy has experienced significant development in a proper political perspective. The dynamics of the first wave of regional head elections in 2015 feature the face of Indonesian democracy nationally. Democratization at the national level is awakened by strengthening democracy at the local level. This paper aims to determine the impact of the Direct Regional Head Election (Pemilihan Langung Kepala Daerah - Pilkada) concurrent in Central Sulawesi to achieve Indonesia’s democratic consolidation. This research was conducted by a qualitative method with a descriptive-analytical approach that explained, described, and analyzed the implementation of the election of Governors and Deputy Governors of Central Sulawesi in 2015 to achieve democratic consolidation. The results showed that simultaneous elections have achieved strengthening democratic consolidation. This condition is seen in several aspects. Namely the development of a free civil society, the development of an open political society; the right rule of law; government effectiveness; and democratic culture development.